2018
DOI: 10.1002/bbb.1931
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting ethanol market volatility: new evidence from the corn implied volatility index

Abstract: Global ethanol production has expanded significantly in recent years as a result of a sharp rise in the worldwide crude oil price. Currently, the USA is the leading producer and exporter of ethanol fuel globally and hence fluctuations in ethanol price could play a vital role in influencing the country's overall bioenergy policy. It is hence important to model and forecast the US ethanol price precisely to minimize the market risk. Surprisingly, this issue has not received considerable attention in the biofuel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…Some were carried out in diesel engines such as Refs [20][21][22][23]. Nithyanandan et al [52] investigated an SI engine using ABE-gasoline blends and found that adding 40% ABE or less affected the combustion substantially. journal.ump.edu.my/ijame ◄…”
Section: In-cylinder Pressure (Icp) and Heat Release Rate (Hrr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some were carried out in diesel engines such as Refs [20][21][22][23]. Nithyanandan et al [52] investigated an SI engine using ABE-gasoline blends and found that adding 40% ABE or less affected the combustion substantially. journal.ump.edu.my/ijame ◄…”
Section: In-cylinder Pressure (Icp) and Heat Release Rate (Hrr)mentioning
confidence: 99%
“…As a result, ethanol is extensively used throughout the world [2,43,44]. Brazil can produce affordable ethanol fuel from the fermentation of sugarcane to supply its transportation sector [45][46][47][48][49][50], whereas the US produces ethanol from corn grain to supply its domestic demands [51][52][53]. However, the use of feedstock from first-generation biofuels such as sugarcane and corn grain to produce ethanol has raised some concerns as it can compete with human food supply [43,54].…”
Section: Introductionmentioning
confidence: 99%
“…In all such cases, production of biofuel crops in urban spaces could potentially contribute. From a policy standpoint, nations have historically acted in accordance with their own unique situations, such as the United States' focus on the economics of maize corn-based ethanol (Dutta, 2019), and France and Germany's adoption of biofuel policies in response to agricultural surpluses in the early 20th century and later the 1970s oil crisis. In many cases, national policy remains driven more by economic self-interest and energy security than global environmental concerns (Oliveira, McKay, & Plank, 2017); however, multinational agreements may offer a more holistic perspective that better recognizes the advantages of small-scale urban biofuel operations.…”
Section: Kingdom and Beyondmentioning
confidence: 99%
“…Furthermore, the inception of biofuel causes a drop in traditional energy prices 2 . It has been suggested that ‘Crude oil prices would be approximately 15–40 US Dollar a barrel higher in the absence of bioethanol production additives.’ 3 …”
Section: Introductionmentioning
confidence: 99%